2002
DOI: 10.1152/ajpgi.00319.2001
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid regulation and glycosylation of mouse intestinal type IIb Na-Picotransporter during ontogeny

Abstract: We sought to characterize expression of an apically expressed intestinal Na-P(i) cotransporter (Na-P(i)-IIb) during mouse ontogeny and to assess the effects of methylprednisolone (MP) treatment. In control mice, Na-P(i) uptake by intestinal brush-border membrane vesicles was highest at 14 days of age, lower at 21 days, and further reduced at 8 wk and 8-9 mo of age. Na-P(i)-IIb mRNA and immunoreactive protein levels in 14-day-old animals were markedly higher than in older groups. MP treatment significantly decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
45
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
7
45
1
2
Order By: Relevance
“…Tissue sections (6-10 m) from both tissues were prepared by the Histopathology Core Service at the University of Arizona (Tucson, AZ). Immunohistochemical staining and detection was performed as previously described (2). NaPi-IIb antiserum was reacted with sections for 60 min at a 1:500 (for intestinal sections) or a 1:4,000 (for lung sections) dilution in PBS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue sections (6-10 m) from both tissues were prepared by the Histopathology Core Service at the University of Arizona (Tucson, AZ). Immunohistochemical staining and detection was performed as previously described (2). NaPi-IIb antiserum was reacted with sections for 60 min at a 1:500 (for intestinal sections) or a 1:4,000 (for lung sections) dilution in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal Pi absorption through the NaPi-IIb cotransporter is regulated by various physiological effectors. Epidermal growth factor (EGF) and glucocorticoids inhibit intestinal sodium-dependent Pi (Na/Pi) absorption and NaPi-IIb gene expression (2,31), whereas 1,25(OH) 2 vitamin D 3 and dietary Pi deprivation stimulate intestinal Na/Pi absorption and NaPi-IIb gene expression (17,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Type II Na ϩ -P i cotransporters (NaPi-II) are largely responsible for renal and intestinal transport of P i in the human body, with the IIa and IIb isoforms being most important in the kidney and intestine, respectively. The NaPiIIa cotransporter is localized on the brush-border membrane of the renal proximal tubules and is regulated by dietary P i levels (6,28,30), parathyroid hormone (15,21), and 1,25(OH) 2 -vitamin D 3 (27). The NaPi-IIb cotransporter is localized on the apical membrane of intestinal enterocytes and is also regulated by dietary P i levels and vitamin D 3 (11,12,32).…”
mentioning
confidence: 99%
“…In addition, recent studies have shown that other physiological factors influence intestinal P i uptake by altering NaPi-IIb cotransporter gene expression. For example, EGF and glucocorticoids decrease NaPi-IIb gene expression, which corresponds to a decrease in intestinal Na-dependent P i absorption (3,34). Conversely, vitamin D 3 (11,32) and estrogen (36) stimulate NaPiIIb gene expression, which corresponds to an increase in intestinal Na-dependent P i absorption.…”
mentioning
confidence: 99%